Changes in drought occurrence and intensity in the context of climate change in Slovakia - L. Labudová; G. Ivaňáková; P. Faško; P. Kajaba; M. Labuda (Theoretical and Applied Climatology, 2024)

Relationship of Morphometrics and Symptom Severity in Female Type I Chiari Malformation Patients with Biological Resilience - Mohamad Motaz Al Samman; Monica A. Garcia; Maitane García; James R. Houston; Dorothy Loth; Richard Labuda; Sarel Vorster; Petra M. Klinge; Francis Loth; Douglas L. Delahanty; Philip A. Allen (The Cerebellum, 2023)

Adult Age Differences in Self-Reported Pain and Anterior CSF Space in Chiari Malformation - Maitane García; Maggie S. Eppelheimer; James R. Houston; Michelle L. Houston; Blaise Simplice Talla Nwotchouang; Kevin P. Kaut; Richard Labuda; J. Rajiv Bapuraj; Jahangir Maleki; Petra M. Klinge; Sarel Vorster; Mark G. Luciano; et al. (The Cerebellum, 2022)

Long‐term changes in drought indices in eastern and central Europe - Jaak Jaagus; Anto Aasa; Svetlana Aniskevich; Boris Boincean; Roxana Bojariu; Agrita Briede; Irina Danilovich; Fernando Domínguez Castro; Alexandru Dumitrescu; Martin Labuda; Lívia Labudová; Krista Lõhmus; et al. (International Journal of Climatology, 2022)
This study analyses long‐term changes in drought indices (Standardised Precipitation Index—SPI, Standardised Precipitation–Evapotranspiration Index—SPEI) at 1 and 3 months scales at 182 stations in 11 central and eastern European countries during 1949–2018. For comparative purposes, the necessary atmospheric evaporative demand (AED) to obtain SPEI was calculated using two methods, Hargreaves‐Samani (SPEIH) and Penman‐Monteith (SPEIP). The results show some relevant changes and tendencies in the drought indices. Statistically significant increase in SPI and SPEI during the cold season (November–March), reflecting precipitation increase, was found in the northern part of the study region, in Estonia, Latvia, Lithuania, northern Belarus and northern Poland. In the rest of study domain, a weak and mostly insignificant decrease prevailed in winter. Summer season (June–August) is characterized by changes in the opposite sign. An increase was observed in the north, while a clear decrease in SPEI, reflecting a drying trend, was typical for the southern regions: the Czech Republic, Slovakia, Hungary, Romania, Moldova and southern Poland. A general drying tendency revealed also in April, which was statistically significant over a wide area in the Czech Republic and Poland. Increasing trends in SPI and SPEI for September and October were detected in Romania, Moldova and Hungary. The use of SPEI instead of SPI generally enhances drying trends.

Three-Dimensional CT Morphometric Image Analysis of the Clivus and Sphenoid Sinus in Chiari Malformation Type I - Blaise Simplice Talla Nwotchouang; Maggie S. Eppelheimer; Paul Bishop; Dipankar Biswas; Janna M. Andronowski; Jayapalli R. Bapuraj; David Frim; Rick Labuda; Rouzbeh Amini; Francis Loth (Annals of Biomedical Engineering, 2019)

Comparison of SPI and SPEI applicability for drought impact assessment on crop production in the Danubian Lowland and the East Slovakian Lowland - L. Labudová; M. Labuda; J. Takáč (Theoretical and Applied Climatology, 2017)

Tracing genetic history of modern humans using X-chromosome lineages - Vania Yotova; Jean-François Lefebvre; Oleksiy Kohany; Jerzy Jurka; Roman Michalski; David Modiano; Gerd Utermann; Scott M. Williams; Damian Labuda (Human Genetics, 2007)

First Molecular Evidence for Puumala Hantavirus in Slovakia - K. Leitmeyer; C. Sibold; H. Meisel; R. Ulrich; M. Labuda; D.H. Krüger (Virus Genes, 2001)

Antimicrobial effects of the macrocyclic Cu(II)-tetraanhydroaminobenzaldehyde complex - S. Jantová; J. Labuda; V. Vollek; M. Zastková (Folia Microbiologica, 1997)